A Synergistic Precursor Regulation Strategy for Scalable Fabrication of Perovskite Solar Cells. Issue 4 (8th March 2021) - Wang, Shubo; Xu, Yibo; Gu, Leilei; Chen, Yiqi; Fan, Jiahao; Qian, Binhui; Li, Ruiyi; Yuan, Ningyi; Ding, Jianning
Abstract : The nucleation and crystallization processes within solution‐processed deposition is key for obtaining perovskite films with high quality. Herein, the synergistic effect of Cs +, ligand solvent (tetramethylene sulfoxide, TMSO), and methylammonium ions (MA + ) on nucleation and crystallization procedures of preparing perovskites films is studied. The results reveal that producing α‐phase nuclei in the intermediate‐phase film (a perovskite film formed by removing the solvent before annealing) is the key factor for obtaining α‐phase‐pure perovskites, wherein Cs + is necessary for reducing the formation energy of the α‐phase. In addition, the nonvolatile ligand (TMSO) is used to inhibit rapid nucleation, because it can form a stable intermediate phase. Furthermore, the introduction of the volatile MA + cations compound (MACl) combined with Cs + contributed to the direct formation of α‐phase nuclei in the intermediate‐phase film, and ion exchange (between FA + and MA + ) occurs during the subsequent annealing process, which leads to the formation of large‐grain perovskite film with good crystallinity. Maximum power conversion efficiencies of 22.08% and 16.88% are obtained via this strategy for a perovskite solar cell on a small area (active area: 0.09 cm 2 ) and a perovskite solar module (aperture area: 12.92 cm 2 ), respectively. Abstract : A large‐grain, phase‐pure, and high‐crystallinity perovskite films is obtained by the synergistic effect of Cs +, MACl, and tetramethylene sulfoxide. An efficiency of 22.08% on small‐area (0.09 cm 2 ) solar cells is achieved and a solar module (aperture area: 12.92 cm 2 ) with efficiency of 16.88% is demonstrated.